First turnover analysis of water-oxidation catalyzed by Co-oxide nanoparticles1. Issue 8 (29th August 2015) - Koroidov, Sergey; Anderlund, Magnus F.; Styring, Stenbjörn; Thapper, Anders; Messinger, Johannes
<x xml:space="preserve">Abstract</x> This paper establishes mass spectrometric 'First Turnover Analysis' after rapid H218O-labelling as method for deriving the mechanism of water oxidation.